2017
DOI: 10.1037/dev0000274
|View full text |Cite
|
Sign up to set email alerts
|

Terminal decline in well-being: The role of multi-indicator constellations of physical health and psychosocial correlates.

Abstract: Well-being is often relatively stable across adulthood and old age, but typically exhibits pronounced deteriorations and vast individual differences in the terminal phase of life. However, the factors contributing to these differences are not well understood. Using up to 25-year annual longitudinal data obtained from 4,404 now-deceased participants of the nationwide German Socio-Economic Panel Study (SOEP; age at death: M = 73.2 years; SD = 14.3 years; 52% women), we explored the role of multi-indicator conste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 80 publications
(119 reference statements)
2
22
0
Order By: Relevance
“…Converging with prior evidence, we found that people who died at younger ages, were less socially active, and suffered from disability or a compromised ability to carry out Instrumental Activities of Daily Living reported lower levels of well-being close to death (see Brandmaier et al, 2017;Windsor et al, 2014). Moving beyond previous reports and demonstrating the power of personality to predict important life outcomes across the entire life span, our results further revealed that personality traits predict late-life well-being above and beyond these well-established predictors.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Converging with prior evidence, we found that people who died at younger ages, were less socially active, and suffered from disability or a compromised ability to carry out Instrumental Activities of Daily Living reported lower levels of well-being close to death (see Brandmaier et al, 2017;Windsor et al, 2014). Moving beyond previous reports and demonstrating the power of personality to predict important life outcomes across the entire life span, our results further revealed that personality traits predict late-life well-being above and beyond these well-established predictors.…”
Section: Discussionsupporting
confidence: 74%
“…The measure has extensively been used in research (Fujita & Diener, 2005;Headey et al, 2010;Lucas, Clark, Georgellis, & Diener, 2003) and taps into cognitive-evaluative facets (rather than affective facets) of wellbeing. To make sure our report is immediately comparable to earlier publications examining terminal decline in well-being (e.g., Brandmaier et al, 2017;, we standardized responses to a T metric (M = 50; SD = 10) with the total 2002 SOEP sample serving as a reference (M = 6.90, SD = 1.81).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…There are currently two software packages for the statistical programming language R that allow fitting SEM trees. One is the semtree package (Brandmaier et al, 2013b) that has been widely applied in the literature (Brandmaier et al, 2013a(Brandmaier et al, , 2016(Brandmaier et al, , 2017(Brandmaier et al, , 2018Jacobucci et al, 2017;Usami et al, 2017Usami et al, , 2019de Mooij et al, 2018;Ammerman et al, 2019;Serang et al, 2020;Simpson-Kent et al, 2020). The other software implementation is the partykit package (Hothorn and Zeileis, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SEM trees as first presented by Brandmaier, Oertzen, McArdle, and Lindenberger (2013), discussed in the methodological literature (Brandmaier, Driver, & Voelkle, 2018;Brandmaier, Prindle, McArdle, & Lindenberger, 2016;Jacobucci, Grimm, & McArdle, 2017;Serang et al, 2020;Usami, Hayes, & McArdle, 2017;Usami, Jacobucci, & Hayes, 2019), and used for data analysis (Ammerman, Jacobucci, & McCloskey, 2019;Brandmaier, Ram, Wagner, & Gerstorf, 2017;Mooij, Henson, Waldorp, & Kievit, 2018;Simpson-Kent et al, 2020) are another popular method for exploring heterogeneity in SEMs that can be considered as a compromise between MGSEMs and latent class models. SEM trees are a data-driven approach that automatically searches through all available covariates to identify groups with similar SEM parameter values.…”
Section: Introductionmentioning
confidence: 99%